Integrating Metabolic Engineering and Heterogeneous Chemocatalysis: New Opportunities for Biomass to Chemicals. Issue 10 (6th May 2016) - Huo, Yanping; Zeng, Huaqiang; Zhang, Yugen
Abstract : Creating breakthroughs : Integrating metabolic engineering process and chemocatalysis system creates tremendous opportunities in biomass transformation. Recently, a breakthrough in the field of applying integrated metabolic process and chemocatalysis systems in biomass transformation has been achieved by combining biocatalysis with electrochemical processes in one pot.